2015
DOI: 10.1245/s10434-015-4681-2
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Magnetic Resonance Sialography for the Evaluation of Radioactive Iodine-Induced Sialadenitis

Abstract: MR sialography images are useful for evaluating RAI sialadenitis, and its findings are in accordance with disease severity. An MR sialographic grading system is suggested to describe the severity of obstructive sialadenitis and SG dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
(20 reference statements)
1
14
0
1
Order By: Relevance
“…A single stenotic lesion of focal type on MR sialography showed better prognosis of patients after sialendoscopic procedures; resolving lesions throughout the entire duct is challenging, especially in stenosis of multiple or diffuse regions. Our results are in accord with those of an earlier study, which suggested that the stenosis type of MR sialography is significantly associated with disease severity of the duct in radioiodine‐induced sialadenitis …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A single stenotic lesion of focal type on MR sialography showed better prognosis of patients after sialendoscopic procedures; resolving lesions throughout the entire duct is challenging, especially in stenosis of multiple or diffuse regions. Our results are in accord with those of an earlier study, which suggested that the stenosis type of MR sialography is significantly associated with disease severity of the duct in radioiodine‐induced sialadenitis …”
Section: Discussionsupporting
confidence: 93%
“…MR sialography has the virtue of visualizing ductal systems in cases of complete obstruction of a distal duct, differently from conventional sialography . It is useful in evaluating preoperative ductal pathology and can allow functional evaluations of SGs using a sialogogue .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms include gland swelling, dysphagia, tenderness, pain, and xerostomia. Diagnostic sialography utilizing ultrasound, magnetic resonance (MR), and computed tomography (CT) has been shown to be a useful adjunct to patient symptoms, though each is limited by facility availability, cost, and physician expertise …”
Section: Introductionmentioning
confidence: 99%